Returns to Education and Individual Heterogeneity - Winfried Pohlmeier; Friedhelm Pfeiffer; Michael Maier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
In this paper, human capital investments are evaluated by assuming heterogeneous returns to education. We use the potential outcome approach to measure the causal effect of human capital investments on earnings as a continuous treatment effect. Empirical evidence is based on a sample of West German full-time employed males from the ?BIBB/IAB-Strukturerhebung 1998/99.? Our estimate of the average treatment effect of an additional year of schooling (ATE) amounts to 8.7%, which is quite similar to conventional instrumental variable estimates.
Keywords: 330; potential outcome approach; marginal benefits and costs of schooling; unobserved heterogeneity; unemployment; average treatment effect; Bildungsertrag; Bildungsinvestition; Berufsbildung; Kosten-Nutzen-Analyse; Schätzung; Deutschland; treatment effect